PENGARUH PERAN ORANG TUA TERHADAP KEMAMDIRIAN BELAJAR SISWA KELAS V SD - Gultom, Pesta Romauli; Siregar, Arifin; Afriadi, Putra; Tamba, Robenhart; Nurmayani, N (Universitas Negeri Medan, 2024)
The aim of this research is to reveal the influence of the role of parents on student independence. This research will discuss the role of parents and student independence. This type of research is quantitative using the ex post facto method. The population in this study were fifth grade students at SD Gugus 35, Onanrunggu District, Samosir Regency with a sample size of 40 students. The sampling technique uses simple random sampling. Data collection techniques used questionnaires and interviews. Data was collected using a questionnaire directly in the field using a shift system, which consisted of a statement of the parental role variable (X) and a statement of the independence variable (Y). Then the data was processed using SPSS version 2.0. The phenomenon that occurs at SD Gugus 35, Onanrunggu District, Samosir Regency is that there are students who are able to make decisions and solve the problems they face themselves. However, there are also students who are still afraid to make decisions and solve their own problems, and to solve these problems students are assisted by their parents. The role of parents is the method used by parents so that later they can become a guide for their children. The role of parents is to help students develop student independence. of 0.133 or 13.3%in the quite strong category. For every additional 1!^ value of the role of parents as a variable (X), student independence (Y) will decrease by 0.021 and vice versa. Looking at the ANOVA table, it is known that Sig is 0.021. So 0.021 <0.05, it can be concluded that H0 is rejected and Ha is accepted, meaning that there is a significant influence of the parental role variable on the independence variable of class V students at Gugus 35 Elementary School, Onanrunggu District, Samosir Regency.